7. ASSESSING THE CHANGE IN SELF-CARE KNOWLEDGE OF CHRONIC OBSTRUCTIONAL LUNG DISEASE PATIENTS AFTER HEALTH EDUCATION INTERVENTION AT VINH CITY GENERAL HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluating the change in self-care knowledge of chronic obstructive pulmonary disease patients at the Department of Internal Medicine, Vinh City General Hospital in 2023 after health education intervention. Research method: Intervention study with before-after comparison. Research on 72 people with chronic obstructive pulmonary disease receiving inpatient treatment at the General Internal Medicine Department of Vinh City General Hospital from May 2023 to November 2023. Results: After the health education intervention, patients’ self-care knowledge changed from good (93.1%) to good (95.8%). In which, knowledge about disease names before intervention (54.2%) after intervention (100%), knowledge about breathing exercises before intervention (16.7%) after intervention (100%), Knowledge about controlled coughing control before intervention (21.3%) after intervention (100%). Conclusion: The rate of self-care knowledge of patients before intervention was rated as good (93.1%). After intervention (95.8%) patients had good self-care knowledge.
Keywords: Health education, self care, knowledge, chronic obstructive pulmonary disease.